Flexural Strength of Different Monolithic Computer-Assisted Design and Computer-Assisted Manufacturing Ceramic Materials Upon Accelerated Aging - Juntavee, Niwut; Juntavee, Apa; Chansathien, Orapun; Prasertcharoensuk, Natcha; Leesuraplanon, Boonsita (European Journal of Dentistry, 2024)
Objectives The durability of ceramic is crucial, which is probably influenced by aging. This study evaluated the effect of aging on flexural strength of different ceramics.Materials and Methods One-hundred twenty ceramic discs (Ø 12 mm, 1.5 mm thickness) were prepared from zirconia-reinforced lithium silicate (ZLS, C), lithium disilicate (LS2, E), precolored yttria-stabilized tetragonal zirconia polycrystalline (Y-TZP, Ip), and customized color Y-TZP (Ic). Samples were randomly divided into two groups for accelerated aging (A) between 5 and 55°C water baths, 30-second immersing time each, for 10,000 cycles, and nonaged group (N), serving as control. Biaxial flexural strength (σ) was evaluated utilizing the piston-on-three-balls at 0.5 mm/min speed. Analysis of variance and Tukey comparisons were determined for significant differences (α = 0.05). Weibull analysis was applied for survival probability, Weibull modulus (m), and characteristic strength (σo). Microstructures were evaluated with scanning electron microscopy and X-ray diffraction (XRD).Results The highest σ and σo were seen for IcN, followed by IcA, IpN, IpA, EN, CA, CN, and EA, respectively. CN showed the highest m, while EA showed the lowest m. Significant differences of σ for each ceramic were indicated (p < 0.05). Aging caused a significant difference in σ (p < 0.05). XRD showed t→m phase transformation of Ip and Ic after aging.Conclusion Aging affected strength of ceramics. Comparable strength between LS2 and ZLS was evidenced, but both were less strength than Y-TZP either aging or non-aging. Comparable strength between precolored Y-TZP and customized color Y-TZP was indicated. Better resisting aging deterioration of Y-TZP than LS2 and ZLS is suggested for fabrication restorative reconstruction.
Keywords: aging; flexural strength; lithium disilicate; monolithic zirconia; zirconia-reinforced lithium silicate